Analysis of Emotional Aspects in Lyrics and Melody of the Traditional Song “Awe Jale” in Sentani Tribe - Kaiway, Yudhi Aji Ristanto; Ardini, Ni Wayan; Yudarta, I Gede (Institut Seni Indonesia Denpasar, 2024)
Purpose: A traditional Sentani song named